Diskresi dan Interpretasi Perhutanan Sosial Indonesia oleh Birokrat Kehutanan Daerah: Temuan Empiris dari Provinsi Daerah Istimewa Yogyakarta - Dwiko Budi Permadi; Hajar Lutviah; Teguh Yuwono; Rohman (Faculty of Forestry Universitas Gadjah Mada, 2022)
Policies on social forestry would be effective when translated into operation by lower forestry bureaucrats. This research aimed to analyze the discretion and interpretation of local forest bureaucrats on Indonesian social forestry policies. This research applied a documentary study, with data collected from policy documents issued by the Provincial Government of DI Yogyakarta and interview materials of 14 source persons from the Local Forest Bureaucrats (LFB) and farmer groups. The results showed that the DI Yogyakarta Provincial Government had produced numerous policy instruments to regulate the mechanism and profit-sharing of social forestry schemes within the Yogyakarta Forest Management Unit (FMU). The discretions proved the bureaucrats prefer forestry partnership cooperation to the licensing schemes. They also preferred utilizing environmental services for nature tourism to timber forest products due to the complexity and complicated harvesting procedures. These preferences were motivated by their views that increasing provincial government revenue and local beneficiaries from the forests were more achievable through partnership schemes and nature tourism. This research indicated a delay in the social forestry implementation through a licensing scheme. However, the creative discretion of the local forest bureaucrats could accelerate the implementation of forestry partnership cooperation schemes.